Peran dan Tujuan Kelompok Tani dalam Sistem Integrasi Jagung dan Sapi di Kecamatan Tenayan Raya Kota Pekanbaru - Linnia Sundary Lubis; Susy Edwina; Evy Maharani (Politeknik Pertanian Negeri Payakumbuh, 2021)
The implementation of the corn and cattle integration system by farmer groups in Tenayan Raya District involves several integrations such as the division of tasks that is not running optimally, the cattle transportation system that is not implemented in a colony using development activities for the transportation of fuel that can be done properly.The research aims to determine the members perception of the role and objectives of the farmer group in the application of corn and cow integration system in Tenayan Raya district Pekanbarucity and analyzing the relationship between the role and purpose of the farmer group in the application of corn and cow integration system Tenayan Raya district Pekanbaru city. This research was conducted in Tenayan Raya district Pekanbaru city. The method use in this research is a survey method with a census sampling technique. Data analysis using quantitative descriptive and a scale to measure a persons perception, and the spearman rank correlation test to measure the relationship between research variables. The results showed that members ' perception of the role of farmer groups in the application of corn and cow integration systems included the category of good enough. Meanwhile, the members perception of Farmer's goals includes very less good category. The relationship between farmer role variables as production units with the goal of better business farmer groups is a strong direct correlation, while the correlation that occurs between farmer group role variables as learning class and rides Cooperation with the purpose of better farming and better living farming group has a weak correlation.